Robert Triffin, Japan and the quest for Asian Monetary Union - Ivo Maes; Ilaria Pasotti (National Bank of Belgium, 2022)
Especially with the Asian financial crisis of 1997-1998, Asian countries have advocated a profound reform of the international financial architecture. Their proposals focused on two main axes: a reform of the global financial system and stronger regional monetary integration in Asia. There are here significant parallels with the ideas of Robert Triffin (1911-1993). Triffin became famous with trenchant analyses of the vulnerabilities of the international monetary system, especially his book Gold and the Dollar Crisis. Triffin put forward several proposals for reforming the global monetary system, but he also developed proposals for regional monetary integration. These were very much based on his experience with the European Payments Union, and focused on the creation of a (European) Reserve Fund and a (European) currency unit. In this paper we focus on Triffin's proposals for an Asian payments union in the late 1960s, giving special attention to Japan (in Triffin's time the biggest Asian economy).
Keywords: A11; B22; B31; E30; E50; F02; F32; 330; Triffin; Bretton Woods; international liquidity; regional monetary integration; Asian Payments Union; Japan